From Electronics Technician to Local Legislator: Pardis and the Dynamics of Electoral Politics in Pesisir Selatan (2001–2024) - Putra, Defri Rahma; Syafrizal, Syafrizal; Armansyah, Armansyah (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2026)
This study examines the biography and political trajectory of Pardis, a local political figure in Pesisir Selatan Regency, West Sumatra, who moved from working as an electronics technician to serving as a member of the Pesisir Selatan Regional House of Representatives (DPRD) for three consecutive terms. This research asks how Pardis’s life history, education, occupational background, and political involvement shaped his career as a local legislator, and what factors enabled him to maintain public trust across the 2014, 2019, and 2024 elections. Using the historical method, this study applies four stages: heuristics, source criticism, interpretation, and historiography. Data were collected through interviews with Pardis and related informants, supported by archival materials, official documents, and relevant literature. The findings show that Pardis was born in Koto Kabun, Nagari Sungai Tunu Utara, Ranah Pesisir District, Pesisir Selatan Regency. He was educated at SDN 16 Koto Kabun, MTsN 5 Pesisir Selatan, SMKS Adi Karya Ranah Pesisir, and ATAK Balai Selasa. His working life began as an electronics technician in 2001 before he entered local politics and was elected to the Pesisir Selatan DPRD in 2014, 2019, and 2024. His electoral success was supported by a leadership style rooted in social proximity, direct field visits, open communication, and active participation in community activities. This study concludes that Pardis’s ability to sustain his political position was shaped not only by formal electoral strategies but also by his long-term capacity to build trust-based relationships with local communities.